Family, material and worldview values and the process of intergenerational transmission - Walęcka-Matyja, Katarzyna Kamila (Kwartalnik Naukowy Fides et Ratio, 2022)
The aim of the research was to analyze the relationships between family and material values and the worldview of parents and their adult children. 68 parents (34 women and 34 men) and their 51 adult children (33 women and 18 men) participated in the study. Parents were in middle and late adulthood (41-67 years), while their children were in early adulthood (18-30 years). The following psychological questionnaires were used: the Material Values Scale (MVS_PL) in the Polish adaptation of Górnik-Durose (2016), the Scale of World Assumptions Scale in the Polish adaptation of Załuski and Gajdosz (2012), the Familism Scale in the Polish study by Walęcka-Matyja (2020) and a questionnaire. The obtained research results indicate a significant stabilization in the parental transmission of family values and beliefs about the world. Intergenerational differentiation was observed in terms of materialistic values.